HUBUNGAN ANTARA MEROKOK DAN GANGGUAN DEPRESI PADA PEGAWAI TETAP LAKI-LAKI UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA PADA TAHUN 2013 - Sulaiman (2013)
moking behavior is a health problem in the world. According to the World Health Organization in 2008, Indonesia was the third-largest number of smokers in the world after China and India with a prevalence of 46.8% for men and 3.1% for women by age 10 years above. Smoking is very bad for health effects, one of which can cause depressive disorders. If seen from the relationship, depression can cause people to smoke, or smoke can cause an increased risk of depression through changes in neurotransmitter line following chronic exposure. The purpose of this study was to determine the relationship between smoking and depressive disorders for men jobholder of Universitas Pembangunan Nasional "Veteran" Jakarta in 2013. This research is descriptive analytical and cross-sectional design with consecutive sampling technique. Each subject was interviewed with the MINI ICD-10 questionnaire to determine diagnosis of depressive disorders and Brinkman Index questionnaire to determine smoking habits. Number of respondents are 62 people. The data were analyzed by univariate and bivariate with Fisher test. The results showed that the incidence of depression of smokers amount to 4 people. The independent variables which been analyzed with bivariate test is smoking degree (p: 0.027) and type of cigarettes (p: 0.016). Both shows that there is a relationship between smoking and depressive disorders. This can be caused by long exposure of nicotine on brain nicotinic cholinergic receptors that can change neurotransmitter line in brain so that can be a risk factor for depressive disorders. Therefore, the public should have been able to change their smoking habits to avoid the risk factors for depressive disorders.